M147 Feasibility Of Delivering An Occupational Health Intervention Aimed At Improving Work Productivity, Among Working Copd Patients. (10th November 2014) - Kalirai, K; Adab, P; Jordan, R; Ayres, JG; Sadhra, S
Abstract : Introduction: There is evidence that workplace productivity may be impaired among working patients with COPD. Occupational health (OH) interventions have been effective in improving work productivity in other chronic conditions. However, little is known about the feasibility and acceptability of such interventions among those with COPD. Aim: To assess feasibility and acceptability of an OH intervention in working COPD patients. Methods: Nested within a primary care COPD cohort (n = 1870), the study included all those who were in work (n = 309). Eligible patients were invited for an interview and assessment with an OH practitioner. The aim was to explore and identify workplace factors that may contribute to their work performance or exacerbate their condition, and to suggest approaches to minimise any respiratory symptoms and improve work capability. Recommendations are sent to the patient, and with their permission, to their GP and employer. The acceptability of the intervention to employers will be explored as a separate part of the study. Results: Of those eligible, 43 (13.9%) agreed to take part and 107 (34.6%) declined. The most common reasons for declining included a perception of being fine at work (49.5%); followed by believing that work adjustments had already been made (7.5%); and worry about involving the employer (4.7%). Patients agreeing to take part were more likely to be male (71.4% vs. 56.2%), ever-smokers (100% vs. 89.5%), slightly older (mean age 61.9 vs. 60.9) and have more severe airflow obstruction (19.5% vs. 12.5%) than those declining. One or more OH recommendations were identified for 14/16 (87.5%) patients seen so far. These included: avoid substances/materials at work (56.3%); modify physical aspects of job (43.8%); modify job tasks/work methods (37.5%); modify work environment (18.8%), change work organisation (31.3%); use respiratory protective equipment (6.3%). Conclusions: This is the first study to assess the feasibility of delivering an OH intervention to patients with COPD working in diverse occupations. Although uptake rates were low, modifiable factors in the work environment that could improve their symptoms and condition were identified for the majority who were assessed. The acceptability of recommendations and feasibility of involving the employer will be further explored.